AUTOMATION OF OPERATIONAL CONTROL OF DATA FLOWS OF THE METALLURGICAL ENTERPRISE ORGANIZATIONAL STRUCTURE - A. N. Chichko; N. V. Andrianov; Ju. V. Jatskevich (Литьë и металлургия)
New method for creation of models of operative control of enterprise is offered. The computer variant of the organizational structure, based on analysis of the charging dynamics of control units, is offered and illustrated at the example of one of organizational structures of Belorussian metallurgical works.